Advanced Node.js development: master Node.js by building real-world applications - Mead, Andrew (PACKT Publishing, 2018)
Advanced Node.js Development is a practical, project-based book that provides you with all you need to progress as a Node.js developer. Node is a ubiquitous technology on the modern web, and an essential part of any web developer’s toolkit. If you're looking to create real-world Node applications, or you want to switch careers or launch a side-project to generate some extra income, then you're in the right place. This book was written around a single goal: turning you into a professional Node developer capable of developing, testing, and deploying real-world production applications. There's no better time to dive in. According to the 2018 Stack Overflow Survey, Node is in the top ten for back-end popularity and back-end salary. This book is built from the ground up around the latest version of Node.js (version 9.x.x). You'll be learning all the cutting-edge features available only in the latest software versions. This book delivers advanced skills that you need to become a professional Node developer. Along this journey you'll create your own API, you'll build a full real-time web app and create projects that apply the latest Async and Await technologies. Andrew Mead maps everything out for you in this book so that you can learn how to build powerful Node.js projects in a comprehensive, easy-to-follow package designed to get you up and running quickly.